Alternative Kind of Radio and Television? A Council of Europe Survey - Flichy, Patrice; Council for Cultural Cooperation, Strasbourg (France). ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1981)
Information from six documents produced by experts to compare and analyze the 21 local and community media experiments they had visited in six countries in 1978 and 1979 is consolidated in this report. This information illustrates the variety of ways that different countries handle local media, and examines the role that such media can play either as an arena for political activism or a center for community resources. Included are an analysis of the coverage area of local radio and television experiments in Belgium, Italy, the United Kingdom, the Netherlands, Ireland and Sweden; a delineation of the number of broadcasting hours for each of the stations visited; and an outline of the financial framework, types of programs, and audiences served by these stations. (MER)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Broadcast Television; Community Resources; Foreign Countries; Mass Media; Media Selection; Programing (Broadcast); Public Television; Radio; Television Research; Europe (West); Reports, Descriptive